2015
DOI: 10.1055/s-0035-1549154
|View full text |Cite
|
Sign up to set email alerts
|

Open Reduction and Internal Fixation of Mandibular Fracture without Rigid Maxillomandibular Fixation

Abstract: Introduction The ability to treat fracture with open reduction and internal fixation (OR/IF) has dramatically revolutionized the approach to mandible fracture. With OR/IF, the postoperative role of rigid maxillomandibular fixation (MMF) has declined, but it is used to maintain proper occlusion until internal fixation of the fracture is achieved. Objective To assess intraoperative manual MMF during OR/IF of selected cases of mandibular fractures. Methods This prospective study was conducted on 80 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Although few European centres were found to use manual MMF routinely in the present study (Table 6), the percentage was significantly greater than that reported by Gear et al 20 The increased use of manual MMF may be justified by the reduced operator and patient risks, including needle-stick injuries, communicable disease transmission, and mucosal and dental injuries. 7,12,18 It is also more economical because it reduces the operative and hospitalisation times, and the cost related to hardware manufacturing and the personnel needed to apply and remove it. 8,13,14,16 However, most authors agree on the need of an experienced assistant to perform manual MMF.…”
Section: Discussionmentioning
confidence: 99%
“…Although few European centres were found to use manual MMF routinely in the present study (Table 6), the percentage was significantly greater than that reported by Gear et al 20 The increased use of manual MMF may be justified by the reduced operator and patient risks, including needle-stick injuries, communicable disease transmission, and mucosal and dental injuries. 7,12,18 It is also more economical because it reduces the operative and hospitalisation times, and the cost related to hardware manufacturing and the personnel needed to apply and remove it. 8,13,14,16 However, most authors agree on the need of an experienced assistant to perform manual MMF.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] In patients with complex facial fractures involving the maxillomandibular unit, the fundamental objective should be to first establish the premorbid occlusion. [7][8][9] Once this has been established, the framework for the remainder of the surgery can be based around the reduced maxillomandibular region. 1 The reasons for this are two-fold.…”
mentioning
confidence: 99%
“…The purposes of the treatment of mandibular fractures are to restore the pre-trauma dental occlusion and normal mouth opening and to reduce the displaced fracture. 4 …”
mentioning
confidence: 99%
“…These factors opened the door for recent studies searching for simpler, faster, easier and at the same time effective OR/IF of the fractured mandible. 4 …”
mentioning
confidence: 99%
See 1 more Smart Citation